DIVERSIFICATION AS A BASIS FOR CREATING AN OPTIMAL PORTFOLIO - Ćerdić, Ivan Mate (International Journal of Economic Practice and Policy, 2015)
Diversification is a method by which we can successfully reduce total risk of created portfolio to the level of market risk, or even lower, depending on which model of diversification investor chooses. At the same time, this was the aim of this reseach – to prove that with properly developed and implemented diversification, portfolio risk can be reduced to the level of systematic risk. Analysing the different examples through this research, that was proven, primarily through the basic hypothesis, in the case od American company IBM and stock index S & P 500. Through the refutation of 1st derivated hypothesis – that diversification across industries can provide advantage over the simple diversification, it was concluded that even with a selection of securities of different sectors of indurstry, systematic risk can not be avoided. In favor of diversification speaks 2nd derivated hypothesis, by which is confirmed that the international diversification is the model of diversification which is the best proved in practice and which largely reduces the risk of created portfolio, even the level of systematic risk can be reduced thanks to investing in securities on the capital markets of different countries.
Keywords: DIVERSIFICATION; PORTFOLIO; risk; yield; securities; systematic risk; market; investing